2014
DOI: 10.3748/wjg.v20.i36.12753
|View full text |Cite
|
Sign up to set email alerts
|

Immune evasion strategies used byHelicobacter pylori

Abstract: Helicobacter pylori (H. pylori) is perhaps the most ubiquitous and successful human pathogen, since it colonizes the stomach of more than half of humankind. Infection with this bacterium is commonly acquired during childhood. Once infected, people carry the bacteria for decades or even for life, if not treated. Persistent infection with this pathogen causes gastritis, peptic ulcer disease and is also strongly associated with the development of gastric cancer. Despite induction of innate and adaptive immune res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
134
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(136 citation statements)
references
References 113 publications
1
134
0
1
Order By: Relevance
“…The triggers for transition from transient or latent infection to clinical illness are also unknown and are likely related to environmental and host genetic factors. A similar phenomena is seen in other chronic infectious diseases in humans such as tuberculosis [66], syphilis [78], and H. pylori gastritis [79]. …”
Section: Map and Susceptibilitysupporting
confidence: 68%
“…The triggers for transition from transient or latent infection to clinical illness are also unknown and are likely related to environmental and host genetic factors. A similar phenomena is seen in other chronic infectious diseases in humans such as tuberculosis [66], syphilis [78], and H. pylori gastritis [79]. …”
Section: Map and Susceptibilitysupporting
confidence: 68%
“…We and others have shown that deacetylation of peptidoglycan allows H. pylori to evade host clearance (5,25-27). Thus, H. pylori has evolved to express an array of diverse phenotypes to subvert obstacles presented by the host (28), and the ability of H. pylori to alter cagY genotypes is yet another mechanism within the repertoire of this organism to evade host defenses.…”
Section: Discussionmentioning
confidence: 99%
“…T. gondii is also found worldwide with prevalence in adult populations ranging from 10% - 80% (Yolken & Torrey, 2008). H. pylori is a bacterium that colonizes the mucosal layer of the gastric epithelium (stomach) and generates a state of chronic inflammation (Lina et al, 2014). Persistent infection with H. pylori causes gastritis, peptic ulcer disease and is associated with other gastric conditions, such as cancer (Lina et al, 2014).…”
Section: Methodsmentioning
confidence: 99%